Perspektif Pengungkapan Tindak Pidana Kebakaran Hutan Dan Lahan Berdasarkan Delik Aduan Masyarakat Di Wilayah Hukum Kepolisian Sektor Reteh - Riki Fernando; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
This study aims to analyze the perspective of uncovering forest and land fire crimes based on public complaints within the jurisdiction of the Reteh Sector Police and to identify the obstacles encountered by police officers during the investigation process. This research employed an empirical legal research method using normative juridical and empirical juridical approaches with a descriptive-analytical design. Data were collected through interviews, observations, and literature studies, then analyzed qualitatively using a deductive approach. The findings indicate that the disclosure of forest and land fire crimes depends not only on investigators' abilities in conducting investigations but also on public complaints as the primary source of information regarding criminal incidents. The main obstacles include limited personnel, extensive jurisdictional areas, difficulties in obtaining evidence, low public participation, and geographical and weather conditions. Efforts undertaken include strengthening inter-agency coordination, integrated patrols, legal awareness programs for the community, and optimizing technological support to improve the effectiveness of law enforcement.